ANALISIS PENGARUH PELATIHAN TERHADAP KINERJA GURU YANG DIMODERASI KECERDASAN EMOSIONAL (Studi Kasus Pada Guru TK Di Kecamatan Rembang) - Maslichan, Maslichan (potensio, 2013)
The purpose of this study was to analyze the effect of training on the performance of teachers who moderated emotional intelligence. The population of this study a number of 243 respondents who are kindergarten teachers in the district Apex. The collected data were analyzed using regression analysis tools operated through SPSS. The results of this study demonstrate that the significant positive effect of training on employee performance, which means, the better training of the employee's performance will also be better. Emotional intelligence in this study proved to be a significant positive effect on employee performance, which means the better the performance of emotional intelligence employees will also be better. While training is moderated by emotional intelligence proved insignificant employee performance.Â Keywords: Training, Emotional Intelligence, and Performance